KECERDASAN LINGUISTIK VERBAL DALAM PENGUASAAN BAHASA ASING - Ali Satri Efendi; Jajang Setiawan; Retno Setya Budiasningrum (JURNAL ILMIAH RESEARCH STUDENT, 2023)
Verbal-linguistic intelligence is a skill possessed by a person in a language. In learning a foreign language, verbal linguistic skills can support and facilitate the process of mastering the language. Many studies have discussed the role of verbal linguistic intelligence in mastering foreign languages. Some of them are included in the literature review in this article. The results of the review conclude that people who have verbal linguistic intelligence have the potential to be able to use their intelligence to develop language skills. With the ability to remember names and places, a person with intelligence in verbal linguistics can master language quite effectively. In mastering a foreign language, a person who learns a foreign language can use his ability to convey ideas and concepts, so that the combination of the ability to remember words and the ability to convey ideas helps the person master the foreign language effectively.